MY SAY: We don't know that we don't know - Abd Razak, Dzulkifli (2010)
Being a global event, the forum was attended by heavyweights in the wireless sector — both commercial and academic — and by regulators such as the Malaysian Communications and Multimedia Commission. As an organisation, the forum was founded in August 2001, and to date has over 140 members from five continents representing all sectors of the mobile communications industry and the research community.The objective of the forum is reportedly to formulate visions on strategic future research directions in the wireless field, among industry and academia, and to generate, identify and promote research areas and technical trends for mobile and wireless system technologies. It hopes to develop a common global vision for the future of wireless to drive research and standardisation.